Energia eólica no estado do Ceará: impactos gerados e contribuição para o desenvolvimento sustentável - Felipe, Tiago José Soares (2014)
The energy issue has worried countries characterized by predominant primary production sector, as well as the so-called industrialized countries - developed or developing countries, like Brazil. This has occurred due to the increase in energy consumption, the modernization of agriculture, the development of the industrial complex, as well as increasing the demand for individual and family comfort. Thus, the availability of energy is one of the most important prerequisites for economic development of nations. Unlike conventional fuels, wind energy is a power source permanently available, abundant, safe, and almost unlimited, with a secure supply of energy. Specifically in Ceará, there is an additional advantage because the seasonality of winds is complementary to the prevailing water regime in hydroelectric generation. When the wind energy potential is most precisely in the period, the rain levels are minimal and costs associated with power generation and risks of deficit are maximum. Thus, it appears that the sum of favorable factors such as availability of wind, the presence of incentives from the federal and state government, and a large sum of investment in this type of clean energy, is enabling the deployment of several wind farms in the state. However, while the supply of electricity has become an indispensable factor to social welfare and economic growth in the state, care must be taken to preserve the environment via environmental licensing regulations. The aim of this study was to analyze the wind energy potential of the state of Ceará and the relationship of the development of the activity with the impacts and the contribution to Sustainable Development in this state. After the survey, we concluded that the appropriate environmental licensing enables appropriate deployment and operation of the activity of energy production from wind power in Ceará, contributing to the achievement of sustainable development in the state.